Clusters Structure, Bonding and Reactivity - Nguyen, Minh Tho.; Kiran, Boggavarapu; SpringerLink (Online service) (Cham : Springer International Publishing : Imprint: Springer, 2017)
The field of atomic clusters continues to attract great interest amongst physicists and chemists alike. This is in part due to their intrinsic properties and potential industrial applications. The first part of Binary Clusters is devoted to recent developments in experimental techniques, the second part covers a variety of theoretical approaches. Different theoretical methods based on group/graph theories and quantum chemical computational methods as well as various spectroscopy techniques (such as mass, laser, infrared, photoelectron etc.) are applied to the determination of the existence of geometrical and electronic structures, chemical bonding phenomena, and the thermodynamic stabilities of several classes of binary clusters. All chapters within this review volume have been contributed by experts in chemistry, physics, and material sciences based at the University of Leuven, Belgium. This book is aimed at professionals and students working in cluster science.
Global Optimisation Strategies for Nanoalloys -- Structural Identification of Doped Silicon Clusters -- Structural Evolution, Vibrational Signatures and Energetics of Niobium Clusters from Nb2 to Nb20 -- Submersion Kinetics of Ionized Impurities into Helium Droplets by Ring Polymer Molecular Simulations Dynamics -- Structure, Stability and Electron Counting Rules in Transition Metal Encapsulated Silicon and Germaniun Clusters -- Transition Metal Doped Boron Clusters: Structure and Bonding of BnM2 Cycles and Tubes -- Silicate Nanoclusters: Understanding their Cosmic Relevance from Bottom-up Modelling -- Magnetic Anisotropy Energy of Transition Metal Alloy Clusters -- Growth Pattern and Size-dependent Properties of Lead Chalcogenide Nanoclusters -- Chemical Reactivity and Catalytic Properties of Binary Gold Clusters: Atom by Atom Tuning in a Gas Phase Approach -- Index.
Keywords: Chemistry, Physical and theoretical; Physical chemistry; Inorganic chemistry; Theoretical Chemistry; Physical Chemistry; Inorganic Chemistry